Parameters optimization and performance evaluation for the novel tuned inertial damper. (1st January 2022) - Baduidana, Marcial; Kenfack-Jiotsa, Aurelien
Abstract: This paper presents a double-flywheels architecture for a novel tuned inertial damper with grounded stiffness device acts as a passive vibration absorber. An undamped primary structure model with a single degree of freedom controlled by the proposed tuned inertial damper is developed and used to derive the equations of motion of the coupled system. The optimum frequency ratio and the optimum damping ratio are found based on the fixed points theory under harmonic force-excited primary structure. Then, the optimum grounded stiffness ratio is deduced. According to the change on the system parameters, there are three cases for the optimum grounded stiffness ratio, i.e., negative, zero and positive. It is found that from these three cases, the proposed tuned inertial damper with positive grounded stiffness device has the best control performance. When compared with some existing dynamic vibration absorbers, the proposed model in this paper in three cases presented the best control performance, featured by the broadest suppression bandwidth and the minimal vibration amplitude of vibration reduction effect under harmonic and random excitation. Highlights: A novel tuned inertial damper with grounded stiffness TID_GSD is proposed. Analytical optimum parameters are fund through fixed-points theory in terms of H ∞ optimization. Numerical simulations are performed in time and frequency domains. The novel TID_GSD provide more improvements with respect to some existing DVAs with or without negative stiffness. The TID_GSD in case 3 resulted in a much smaller primary system frequency response than its static response without control.